Corrigendum: Vulnerable period in heart failure: a window of opportunity for the optimization of treatment - a statement by Mexican experts - José Antonio Magaña Serrano; José Angel Cigarroa López; Adolfo Chávez Mendoza; Juan Betuel Ivey-Miranda; Genaro Hiram Mendoza Zavala; Luis Olmos Domínguez; Sergio Armando Chávez Leal; José Ernesto Pombo Bartelt; Eduardo Heberto Herrera-Garza; Gerardo Mercado Leal; Rodolfo Parra Michel; Luisa Fernanda Aguilera Mora; et al. (BioExcel Publishing Ltd, 2024)
The authors wish to make the following corrections to their article: Magaña Serrano JA, Cigarroa López JA, Chávez Mendoza A, Ivey-Miranda JB, Mendoza Zavala GH, Olmos Domínguez L, Chávez Leal SA, Pombo Bartelt JE, Herrera-Garza EH, Mercado Leal G, Parra Michel R, Aguilera Mora LF, Nuriulu Escobar PL. Corrigendum: Vulnerable period in heart failure: a window of opportunity for the optimization of treatment - a statement by Mexican experts. Drugs Context. 2024;13:2023-8-1. https://doi.org/10.7573/dic.2023-8-1